The parent advantage in fostering children's e-book comprehension - Dore, Rebecca A.; Hassinger-Das, Brenna; Brezack, Natalie; Valladares, Tara L.; Paller, Alexis; Vu, Lien; Golinkoff, Roberta Michnick; Hirsh-Pasek, Kathy (Early childhood research quarterly)
•With audio narration, young children can use e-books independent of adults.•Little research has investigated the efficacy of e-book audio narration for learning.•Preschoolers read e-books with audio narration, without narration, or with a parent.•Children learned some content from e-books using audio narration.•Children recalled most about the e-book after reading with a parent. One potential advantage of e-books is that unlike traditional books, preschoolers can read independent of an adult by using the audio narration feature. However, little research has investigated whether children comprehend a story's content after using an e-book with audio narration. The current study compares preschoolers' comprehension of an e-book in three conditions: (1) parent reading, in which parents read the e-book to their children, (2) independent with audio, in which children see the e-book independently with audio narration, and (3) independent without audio, in which children see the e-book independently but do not have audio narration available. Our results suggest that children comprehend some content from e-books using audio narration, indicating that using e-books independently may be a worthwhile activity for preliterate children while caregivers are otherwise occupied. However, results also show that children recall the most information about the e-book after reading with a parent.